1997
DOI: 10.1038/sj.leu.2400585
|View full text |Cite
|
Sign up to set email alerts
|

Second allogeneic bone marrow transplantation in acute leukemia: a multicenter study from the Gruppo Italiano Trapianto Di Midollo Osseo (GITMO)

Abstract: Thirty-eight second allogeneic bone marrow transplants (BMT)of 25-70%. The positive prognostic factors reported were not for acute leukemia relapsed after first BMT were performed in homogeneous and their identification was precluded in most Twenty-four patients were male and 14 female, median age

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
47
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 3 publications
4
47
0
Order By: Relevance
“…3,4,12 On univariate analysis in our study, we found that longer time to treatment failure from the first transplant was associated with a longer PFS from the second transplant, a finding that is consistent with that seen with registry data (Table 4). Although persistence of disease at the time of transplant showed a trend towards a poorer PFS (hazard ratio 1.69, 95% confidence interval 0.78-3.69), we were not able to demonstrate statistical significance for this factor, which might be attributed to our small patient numbers.…”
Section: Discussionsupporting
confidence: 80%
“…3,4,12 On univariate analysis in our study, we found that longer time to treatment failure from the first transplant was associated with a longer PFS from the second transplant, a finding that is consistent with that seen with registry data (Table 4). Although persistence of disease at the time of transplant showed a trend towards a poorer PFS (hazard ratio 1.69, 95% confidence interval 0.78-3.69), we were not able to demonstrate statistical significance for this factor, which might be attributed to our small patient numbers.…”
Section: Discussionsupporting
confidence: 80%
“…Some recent studies suggest that young patient age and better supportive care (in more recent years) are stronger predictors of survival than the interval between the two HCT. 30,31 While the median age of patients in our study was 25 months, their survival may have been more significantly influenced by the year of transplant. Eighty percent of children (four of five) transplanted after 1994 survived compared with only 17% (one of six) receiving HCT before 1994.…”
Section: Discussionmentioning
confidence: 91%
“…Our data, as well as other reports, indicate that length of remission after first transplantation is probably the most important variable predicting outcome after second transplant. 1,3,15,[17][18][19][20][21] Relapse, treatment failure and mortality are higher in patients with early relapse. We defined early relapse as occurring within 6 months after first transplant.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,[13][14][15][16][17][18][19][20][21] Thus far, most studies of second transplants for recurrent leukemia are limited by small numbers of patients with heterogeneous prognostic factors. While early relapse after first transplantation and advanced disease status at second transplantation predict poor outcome, data on other factors that may affect outcomes such as conditioning regimen and use of a different donor are few.…”
Section: Discussionmentioning
confidence: 99%